Numerical aerodynamic database in elite male runners - Beaumont, F.; Delouis, P.; Polidori, G. (International Journal of Sports Science & Coaching, 2022)
This study is motivated by a real lack of quantitative data concerning the aerodynamic forces exerted on world-class runners during running events. The objective of this study is to create a database representative of the morphological diversity of runners but also of the speed which is closely related to the running event. A numerical method was used to estimate the aerodynamic forces exerted on runners of size between 1.6 and 2 m and for speeds ranging from 10 to 40 km/h. The results presented in this study suggest that the aerodynamic force is inherent to two main parameters: the size of the runner which affects the body frontal area and the speed which depends on the running discipline (100 m, middle- or long-distance running…). One of the main results of this study is that, regardless of running speed, the drag force increases by about 56% for a runner's height between 1.6 m and 2 m (frontal area between 0.383 m2 and 0.596 m2). These data could be very useful to determine the value of the horizontal drag forces applied to the runner's waist during physiological measurements performed on a treadmill.